2012
DOI: 10.1186/1472-6963-12-371
|View full text |Cite
|
Sign up to set email alerts
|

Study Protocol: Screening and Treatment of Alcohol-Related Trauma (START) – a randomised controlled trial

Abstract: BackgroundThe incidence of mandibular fractures in the Northern Territory of Australia is very high, especially among Indigenous people. Alcohol intoxication is implicated in the majority of facial injuries, and substance use is therefore an important target for secondary prevention. The current study tests the efficacy of a brief therapy, Motivational Care Planning, in improving wellbeing and substance misuse in youth and adults hospitalised with alcohol-related facial trauma.Methods and designThe study is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 46 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…These places are the primary sites of the Indigenous assaults in the Northern Territory urban area. Alcohol-related violent assaults among the Indigenous population leads to high incidences of facial trauma patients at Royal Darwin Hospital (Jayaraj, Thomas, Kavanagh, et al, 2012;Jayaraj et al, 2013;Nagel, Jayaraj, Ah Kit, Thompson, & Spencer, 2010).…”
Section: Alcohol-related Violent Assaultsmentioning
confidence: 95%
See 2 more Smart Citations
“…These places are the primary sites of the Indigenous assaults in the Northern Territory urban area. Alcohol-related violent assaults among the Indigenous population leads to high incidences of facial trauma patients at Royal Darwin Hospital (Jayaraj, Thomas, Kavanagh, et al, 2012;Jayaraj et al, 2013;Nagel, Jayaraj, Ah Kit, Thompson, & Spencer, 2010).…”
Section: Alcohol-related Violent Assaultsmentioning
confidence: 95%
“…Indigenous drinkers commonly migrate from the rural and remote communities, where access to alcohol is restricted, to Darwin and Alice Springs to engage in binge drinking activity with family members and friends (Jayaraj, Thomas, Thomson, et al, 2012). Binge drinking among the Indigenous population is often funded by government Centrelink allowances.…”
Section: Payday Bingementioning
confidence: 99%
See 1 more Smart Citation
“…Although Brazilian law prohibits the sale of alcoholic beverages to minors (Law n° 9294, July 15, 1996), the consumption of alcohol is commonplace among adolescents either in the home or in the public environments. Alcohol intake is also considered a risk factor for antisocial behaviour, criminal behaviour, poor scholastic performance, interpersonal violence, injuries, and traffic accidents, which can result in TDI and maxillofacial trauma. Thus, the 23.1% prevalence rate of binge drinking in a population of 12‐year‐olds is worrisome due to the possible consequences with regard to dependence, systemic health problems, and dental/maxillofacial trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Carrasco et al studied 479 cases of deaths from motorcycle crashes in Campinas and observed the following: 90.8% were male, the mean age was 27.8 (range: 0-73) and blood alcohol was positive in 42.2% of the victims (mean score: 0.627 g/L), corroborating the fact that alcohol is a significant factor in relation to accidents and is an important risk factor contributing to fatal collisions 6 . Laws and prevention programs are an excellent long-term solution in reducing traffic-related trauma and general trauma rates [7][8][9] . An excellent example of such an initiative is Sunnybrook RBC First Office for Injury Prevention, which was established in 1986 within Sunnybrook's Trauma, Emergency and Critical Care department, in Toronto.…”
mentioning
confidence: 99%